2012
DOI: 10.1002/stem.1071
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of TPO‐Expanded CD34 + Cord Blood Cells Identifies CD34 CD61 Cells as Platelet‐Producing Cells Early After Transplantation in NOD/SCID Mice and rCD34 + Cells as CAFC Colony‐Forming Cells

Abstract: Transplantation of thrombopoietin (TPO)‐expanded cord blood CD34+ cells accelerates human platelet recovery in NOD/SCID mice. It is unknown which subpopulations of the TPO‐expanded cells mediate accelerated platelet recovery and bone marrow (BM) engraftment. In this study, the contribution of these subpopulations to human platelet appearance in the blood and BM engraftment was studied in NOD/SCID mice. Following transplantation of CD34−/CD61−/lineage− cells (Lin−), human platelets were detected in the blood of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…The studies presented in this article build on our previous short-term (6 week) engraftment studies with single CB transplants in immune-deficient mice, where we have shown that TPO treatment can improve early platelet recovery and that this recovery is mostly dependent on the TPO mediated generation of CD34 -CD61 -cells [44,51]. Importantly, in our current studies, by analyzing engraftment using donorspecific HLA antibodies in the dCB transplant setting, we could further demonstrate that this improved in vivo early platelet recovery (around day 7) was indeed originating from TPO treated CD34 + cell graft, whereas the untreated CD34 + cells formed platelets at later time points (significantly from around week 2) and dominated over the TPO cultured cells.…”
Section: Van Der Garde Et Almentioning
confidence: 93%
See 3 more Smart Citations
“…The studies presented in this article build on our previous short-term (6 week) engraftment studies with single CB transplants in immune-deficient mice, where we have shown that TPO treatment can improve early platelet recovery and that this recovery is mostly dependent on the TPO mediated generation of CD34 -CD61 -cells [44,51]. Importantly, in our current studies, by analyzing engraftment using donorspecific HLA antibodies in the dCB transplant setting, we could further demonstrate that this improved in vivo early platelet recovery (around day 7) was indeed originating from TPO treated CD34 + cell graft, whereas the untreated CD34 + cells formed platelets at later time points (significantly from around week 2) and dominated over the TPO cultured cells.…”
Section: Van Der Garde Et Almentioning
confidence: 93%
“…Blood collection and human platelet measurements were performed as described previously [47,48,51]. Briefly, human platelets were stained with noncross reactive mouse anti-human CD41-PE and human CD45 cells were stained with mouse anti-human CD45-PC7 (both Beckman Coulter).…”
Section: Analysis Of Pb After Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although they may provide a more definitive assessment of MK progenitor numbers, they are time-consuming, do not allow realtime evaluation and, since the colonies are the product of the proliferation of MK progenitors, they do not allow the analysis of the MK progenitor itself. However, MK progenitors can also be characterized by their expression of a range of cell surface markers, including CD41a and CD61 [13][14][15]. Such assessments can be performed rapidly and provide the potential for real-time assessment of MK progenitor cell numbers, prospective isolation, additional analyses, and therapeutic application.…”
Section: Introductionmentioning
confidence: 99%